2021
DOI: 10.1007/s13555-021-00539-3
|View full text |Cite
|
Sign up to set email alerts
|

Chlormethine Gel for the Treatment of Skin Lesions in All Stages of Mycosis Fungoides Cutaneous T-Cell Lymphoma: A Narrative Review and International Experience

Abstract: Mycosis fungoides (MF), the most common form of primary cutaneous T-cell lymphoma, is a disease typically with an indolent course that is initially characterized by localized patches and plaques. In the early stages of the disease, treatment involves skin-directed therapies (SDTs) such as topical corticosteroids and retinoids. Chlormethine gel (also known as mechlorethamine) was the first SDT purposely developed to treat MF and is currently endorsed by international guidelines for the treatment of adult patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
48
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(56 citation statements)
references
References 47 publications
(57 reference statements)
6
48
1
Order By: Relevance
“…Herein, an additional 7 months of follow-up was included for patients who enrolled in study 202 and were treated with 0.04% chlormethine gel. In clinical practice, patients often initiate treatment with chlormethine gel at a lower frequency than once daily and increase frequency of application over time, in part to avoid the development of AEs [19,20,23]. Nevertheless, our analysis on patients from pivotal studies found no association between the frequency of chlormethine gel application and the occurrence of skin-related AEs, despite once-daily application.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Herein, an additional 7 months of follow-up was included for patients who enrolled in study 202 and were treated with 0.04% chlormethine gel. In clinical practice, patients often initiate treatment with chlormethine gel at a lower frequency than once daily and increase frequency of application over time, in part to avoid the development of AEs [19,20,23]. Nevertheless, our analysis on patients from pivotal studies found no association between the frequency of chlormethine gel application and the occurrence of skin-related AEs, despite once-daily application.…”
Section: Discussionmentioning
confidence: 77%
“…As the mode of action is purported to be the same for chlormethine gel and ointment formulations, the difference in time to response could be due to differences in the composition and/or drug delivery of the two formulations. The gel formulation contains the excipient Klucel™ [21] that ensures appropriate viscosity of the product and makes the gel more likely to remain at the site of administration and at the target area [20]. In-vitro permeation studies have indicated that chlormethine gel remains in the epidermal layer, with minimum levels reaching dermal tissue [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cutaneous lymphoma clinics have had good experiences with CL gel for patients with MF [ 55 , 56 ], and several clinical studies have investigated CL gel treatment in a real-world setting. Here, cohort studies with more than ten patients are discussed.…”
Section: Efficacy Of CL Gel Treatmentmentioning
confidence: 99%
“…Among lymphomas with cardiac involvement, the most common type of pathology is diffuse large B-cell lymphoma (58%), whereas T-cell lymphoma is quite rare (16%) ( 2 ) And 62% of patients with peripheral T-cell lymphoma present with extranodal diseases ( 7 ). T-cell lymphoma has been reported to involve the skin ( 8 ), heart ( 9 ), central nervous system (CNS) ( 10 ), intestine, and lungs ( 11 ). Also, 23% of primary cardiac lymphomas are presented with arrhythmias and AVB is even more rare at 8% ( 12 ).…”
Section: Discussionmentioning
confidence: 99%